Glucose control and cardiovascular outcomes: reorienting approach - Khardori, Romesh; Nguyen, Diep (Frontiers in Endocrinology, 2012)
Cardiovascular disease accounts for nearly 70 % of morbidity and mortality in patients with diabetes mellitus. Strides made in diabetes care have indeed helped prevent or reduce the burden of microvascular complications in both type-1 and type-2 diabetes. However, the same can’t be said about macrovascular disease in diabetes. Several prospective trials so far have failed to provide conclusive evidence of glycemic control superiority in reducing macrovascular complications or death rate in people with advanced disease or those with long duration of diabetes. There are trends that suggest that benefits are restricted to those with lesser burden and shorter duration of disease. Furthermore, it is also suggested that benefits might accrue but it would take longer time to manifest. Clinicians are fraught with challenge to decide how to triage patients for intensified care versus less intense care. This review focusses on evidence and attempts to provide a balanced view of literature that has radically affected how physicians treat patients with macrovascular disease. It also takes cognizance of the fact that natural course of disease may be changing as well possibly related to better overall awareness and possibly improved access to information about better individual healthcare. The review further takes note of some hard held notions about pathobiology of disease that must be interpreted with caution in light of new emerging data. In light of recent developments ADA and EASD have taken step to provide some guidance to clinicians through a joint position statement. A lot more research would be required to figure out how best to manage macrovascular disease in diabetes mellitus. Glucocentric stance would have to yield to evidence based, and possibly, concurrent multifactorial intervention to enhance quality of care that is safe and effective.